Strong configuration interaction in the double ionization spectra of noble gases studied by the relativistic propagator method - Pernpointner, Markus; Zobel, J. Patrick; Kryzhevoi, Nikolai V. (Physical review. A, Atomic, molecular, and optical physics, 2012)
In this work, the four-component two-particle propagator technique is employed for the calculation of double ionization spectra of the noble gas atoms Ne through Rn. For a correct assignment of the individual final states, inclusion of spin-orbit coupling and electron correlation is mandatory and is accounted for in the framework of the relativistic propagator. It was observed that the ns2np4(3P2,1,0, 1D2, 1S0) manifolds of all investigated noble gas dications exhibit a clear main-state character with only small admixture from other configurations. This also refers to the 2s12p5(3Po2,1,0, 1Po1) states of Ne2+. In the argon, krypton, and xenon dications, the ns1np5(3Po2,1,0) states, and especially the ns1np5(1Po1) ones, lose intensity due to pronounced configuration interaction. These states experience strong mixings with ground-state shake-up satellites, which occupy the same energy region. The composition of the 5s15p5(1Po1) singlet state of Xe2+ is studied in detail by analyzing the corresponding eigenvector. As long as a LS coupling picture can be approximately maintained, the amount of singlet-triplet splitting decreases in the sequence from neon to xenon. In the 6s16p5 manifold of Rn2+, a complete disappearance of well-defined main states takes place leading to a dense and complicated spectrum governed by very strong multiconfiguration effects. Relativistic corrections to the Coulomb interaction are accounted for by inclusion of the Gaunt (magnetic) term.